Innovations in insuring the poor: Providing insurance through microfinance institutions: The Indian experience - Ruchismita, Rupalee; Varma, Sona (International Food Policy Research Institute, 2009)
Microinsurance is a powerful tool in helping low-income households transition out of poverty, but it has not achieved substantial scale compared with microcredit. In India, microfinance institutions (MFIs) initially showed great potential in offering microinsurance through in-house provision (the mutual model) or as agents for mainstream microinsurance companies (the partner– agent model). Over time, however, both models revealed significant flaws. The mutual model appeared limited because the community absorbs all the risk, and the partner–agent model experienced severe implementation issues, causing many large MFIs in India to scale back its use. The microinsurance industry is battling the challenges of an infant industry—challenges made more severe by the difficulty of providing high-quality services at a price that the target population is willing to pay. Yet slow progress and the experiences of a few MFIs offer hope that MFIs can become a suitable delivery channel for microinsurance products. This brief examines the merits of providing microinsurance through MFIs in light of the challenges faced by the microinsurance industry. The brief highlights the experience of Indian MFIs, though a number of issues are globally relevant.